Evaluasi Sistem Penilaian Maturitas Sistem Pengendalian Intern Pemerintah (SPIP) Pada Pemerintah Daerah - Mukhlis Mukhlis; Sumirah Sumirah; Adhitya Latif Prahesta (Politeknik Negeri Batam, 2021)
The purpose of this research is to identify problems existing in the maturity assessment system of Government Internal Control System (SPIP) based on the Regulation of the Head of Finance and Development Supervisory Agency (BPKP) Number 4 of 2016 and provide the solutions. The research method was qualitative, using primary data through interview and focus group discussion. Secondary data were in the form of laws and regulations, guidelines, as well as maturity assessment instrument for SPIP. The data analysis used an interactive model. This research found that the current assessment system did not direct the assessment team and quality assurance team to perform an analysis of relationship among SPIP indicators and between SPIP indicators and other governance indicators. In addition, the scoring system is considered to be emphasized more on the fulfillment of administrative evidence rather than the substance of the assessment. Therefore, the assessment system should consider the relationship of variables in the assessment process and put forward the substance of the assessment rather than the completeness of documentation. Keywords: SPIP, control, measurement, maturity